An Integrated Blockchain-Enabled DMAIC Framework to Optimise Aviation MRO Procurement in Indonesia - Basri Fahriza; Adibah Shuib; Wan Mazlina Wan Mohamed (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines persistent procurement inefficiencies in Indonesia’s aviation Maintenance, Repair, and Overhaul (MRO) sector, including prolonged lead times, customs delays, and dependency on imported spare parts. To address these challenges, the research develops the Integrated Blockchain-Based Framework for Aviation MRO Procurement (iBF-AMP) using the Lean Six Sigma DMAIC (Define, Measure, Analyse, Improve, Control) methodology. Data were obtained through expert interviews, process mapping, and benchmarking against international best practices. The findings suggest that the iBF-AMP can reduce procurement cycle time from 11–18 days to 5–7 days by enabling digitalised supplier interaction, automated smart contract–based documentation, and centralised warehousing in the Batam Free Trade Zone. The framework also improves customs efficiency through blockchain-enabled traceability and enhances supplier accountability via transparent digital ledgers. By integrating Lean Six Sigma with blockchain technology, the model offers a scalable pathway to strengthen efficiency, transparency, and reliability in aviation logistics, particularly for emerging economies.   Keywords: Lean Six Sigma; DMAIC; Blockchain; Smart Contracts; Aviation MRO; Procurement